Lead in Chinese villager house dust: Geographical variation and influencing factors. (December 2015) - Bi, Xiangyang; Liu, Jinling; Han, Zhixuan; Yang, Wenlin
Abstract: House dust has been recognized as an important contributor to Pb exposure of children. Here we conducted a comprehensive study to investigate geographical variation of Pb in Chinese villager house dust. The influences of outdoor soil Pb concentrations, dates of construction, house decoration materials, heating types, and site specific pollution on Pb concentrations in house dust were evaluated. The concentrations of Pb in 477 house dust samples collected from twenty eight areas throughout China varied from 12 to 2510 mg/kg, with a median concentration of 42 mg/kg. The median Pb concentrations in different geographical areas ranged from 16 (Zhangjiakou, Hebei) to 195 mg/kg (Loudi, Hunan). No correlations were found between the house dust Pb concentrations and the age of houses, as well as house decoration materials. Whereas outdoor soil, coal combustion, and site specific pollution may be potential Pb sources. Principal component analysis (PCA) confirmed that elemental compositions of the house dust were controlled by both anthropogenic and geogenic sources. Using scanning electron microscopy (SEM), the Pb bearing particles in the house dust were also studied. Highlights: Geographical variation in house dust Pb concentrations were observed. Dust Pb concentrations were not associated with house age and decoration materials. Soil, coal combustion, and site specific pollution were potential Pb sources. Pb bearing particles were identified by SEM-EDX. Abstract : The variations of Pb in Chinese villager house dust were controlled by outdoor soil, coal combustion, and site specific pollution sources.